Answer:
![x=-9](https://tex.z-dn.net/?f=x%3D-9)
![y=4](https://tex.z-dn.net/?f=y%3D4)
Step-by-step explanation:
← Equation 1
![4(-2y+x)-9x=13\\](https://tex.z-dn.net/?f=4%28-2y%2Bx%29-9x%3D13%5C%5C)
By simplifying the above equation we get,
(Simplifying the brackets)
(By subtracting
from
) ← Equation 2
Multiply Equation 1 by 5 and Equation 2 by 3 and add them together.
Equation 1 multiplied by 5 will give,
![15x+50y=65](https://tex.z-dn.net/?f=15x%2B50y%3D65)
Equation 2 multiplied by 3 will give,
![-24y-15x=39](https://tex.z-dn.net/?f=-24y-15x%3D39)
Add those together,
(After simplifying
values)
Therefor ![y=4](https://tex.z-dn.net/?f=y%3D4)
By substituting
to Equation 1 we get,
![3x+10*4=13](https://tex.z-dn.net/?f=3x%2B10%2A4%3D13)
![3x+40=13\\3x=-27\\x=-9](https://tex.z-dn.net/?f=3x%2B40%3D13%5C%5C3x%3D-27%5C%5Cx%3D-9)
Therefor we can say,
![x=-9](https://tex.z-dn.net/?f=x%3D-9)
![y=4](https://tex.z-dn.net/?f=y%3D4)